ANALYSIS OF INTEREST IN BUYING MAYBELLINE COSMETICS WITH THE INFLUENCE OF SOCIAL MEDIA, PRODUCT QUALITY AND PRICE - Nuraeni Nuraeni; Agustini Tanjung; Dadang Heri Kusumah; Primaraga Sumantri Indra Wicaksana (Jurnal Ekonomi, 2023)
For a woman appearance and beauty is one of the most important things. Maybelline is one of the favorite beauty cosmetic brands for some women in Indonesia. There are many cosmetic competitors in Indonesia, but still Maybelline is still one of the best-selling beauty products traded in Indonesia. This study aims to determine, examine, and analyze how the influence of social media, quality and price on buying interest. This research was conducted on people who live in South Cikarang. With a total of 112 respondents. This study uses a quantitative approach and the data used are primary data obtained from the distribution of questionnaires conducted online. The method used in this study is the multiple linear regression method using the IBM SPSS version 23 software application. The results of this study indicate that: (1) social media has a positive effect on buying interest, (2) quality does not have a positive effect on buying interest, (3 ) Price also has a positive effect on the interest in buying Maybelline cosmetics in the people of South Cikarang.